The Effect of Oil Price Volatility on Economic Activity: New Evidence from Iraq - Mohamad Khan , Twana N. (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract: Global oil markets witnessed intense price volatility in the recent years. Volatility of crude oil price is perceived as a significant source of economic fluctuation. It could likely affect levels of economic growth whether in oil exporting or in oil importing countries. In addition, Iraq is one of the leading oil exporting countries in the world. In general, the national income of the country is depending on crude oil. Oil revenues in Iraq cover above % 90 of the Iraqi government's budget every year since the collapse of the Saddam’s regime in 2003, and the rising of crude oil price recently affects the economic growth in Iraq. Moreover, the main purpose of this study is to examine the effects of oil price volatility on economic activity in Iraq. For this purpose, this study employs an ARDL time series model over the period of 1986–2022. In addition, the time series datasets employed in the study are tested for both stationarity and co-integration model by using the augmented Dickey-Fuller (ADF) unit root and Johansen test for co-integration test respectively. According to our results we have found that there is a significant and negative relationship between oil price volatility and economic activity in Iraq for that period. Keywords: Oil price volatility, economic activity, ARDL Model, Iraq.